Optimal Public Expenditure in Developing Countries - Khac Lich, Hoang (VNU JOURNAL OF ECONOMICS AND BUSINESS; Vol 35 No 2, 2019)
Many researchers believe that government expenditure promotes economic growth at the first development stage. However, as public expenditure becomes too large, countries will suffer a huge tax burden and tax distortions. This suggests there is an optimal public expenditure at which the economic growth rate is the highest. However, the optimal point would differ across countries because of differences in economic structure. In this present paper, the optimal public expenditure in developing countries is analyzed. Based on descriptive statistics and regression analysis of 30 developing countries in the period 2004-2013, the findings of this paper are threefold: (i) public expenditure increases along with the development level of countries; (ii) optimal public expenditure is at 19.375% of GDP; (iii) economic growth has a positive relationship with both investment and the labor force, and a negative relationship with urbanization.